Bioactivity of a Compound of Standardized Bangle (Zingiber cassumunar Roxb.) Extract Fraction as a Complimentary Therapy to Prevent Malaria Complications - Hermansyah, Bagus; Utami, Wiwien Sugih (Medical Faculty of Jember University (Fakultas Kedokteran Universitas Jember), 2015)
Malaria is still a major problem in the international and national scale. World Health Organization (WHO) states that based on World malaria report, world cases of malaria reached 216 million and an estimated of 655 thousand people died, in 2010. Overproduction of pro-inflammatory cytokines by phagocytic cells and activated endothelial cells occurs In the severe malaria. Bangle (Zingiber cassumunar Roxb.) has the potential to be developed as a new complementary therapy that is expected to prevent fatal malaria complications. The research objective is to test in vivo, the activity of a compound of standardized Bangle (Zingiber cassumunar Roxb.) fraction extract as a complementary therapy along with standard anti-malarial drug, artemisin. This is a true experimental study using twenty-five mice Balb / C male which are divided into five groups; the negative control group, positive control group treated KI, II, and III stimulation with each of the compounds of standardized fraction extract of bangle ( FEBT-h, FEBT-dcm, FEBT-m) for 14 days. Oneway ANOVA test showed the result of p = 0.01 (p <0.05). Continued with LSD test that showed the most significant in lowering the degree of parasitaemia is the group of methanol (FEBT-m).Keywords: Zingiber cassumunar Roxb, fractionated extracts, complementary therapies, malaria